The Future of Food in the Caribbean: Climate Change and Food Security - Donna Miller (Caribbean Studies Students' Union, 2023)
1.5 Stay Alive is a nature film, music video-like documentary that emphasizes the consequences of a 1.5 degree increase in temperature that would negatively impact the Caribbean region ("1.5 Stay Alive: Science Meets Music in the Caribbean"). The film demonstrated the role that developed countries play in advancing and maintaining the climate crisis in the Caribbean. Disaster capitalism describes the exploitation by developed countries when responding to crises, intentionally creating a more unequal and undemocratic society. Using the example of Hurricane Maria, Klein states that Puerto Rico became broken because of deliberate, systematic interferences to power, water, health, communication, and food systems (2018). Alternatively, developed countries may supply the Caribbean with funds to produce and distribute locally grown produce. An example of what may be done with these funds can be seen in Cuba which created a self-sufficient urban agricultural economy. This would strengthen food security and increase the ability and knowledge to build back food systems following the effects of climate change (Quirk 2012). Information omitted includes details on how developed countries contributed to climate change vulnerabilities in the Caribbean. Environmental changes shape Caribbean agricultural trends which are already historically vulnerable owing to the by-products of colonial and plantation economies (Barker 2012, 42). The film advances the understanding of the effects of global warming in the Caribbean by not only showing the scientific perspective, but also the human side. Climate change affects more than just infrastructure, coral reefs, and economies, but it also affects people's lives.